2014
DOI: 10.4238/2014.october.31.10
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 gene -592C>A polymorphism and susceptibility to gastric cancer

Abstract: ABSTRACT. Numerous studies have evaluated the association between the human interleukin-10 gene -592C>A polymorphism and gastric cancer risk. However, the results have been inconsistent. This meta-analysis was designed to resolve these controversies. Systematic searches of the electronic databases Embase, PubMed, and Google Scholar were performed to identify relevant studies. A meta-analysis was performed to examine the association between the interleukin-10 gene -592C>A polymorphism and gastric cancer risk. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…IL-10 rs1800896 polymorphism G allele has been shown to cause higher IL-10 production [10], which may further lead to carcinogenesis. Some studies have illustrated that the IL-10 rs1800896 polymorphism was correlated with enhanced risk of nasopharyngeal carcinoma [25] and gastric cancer [26], diabetic nephropathy [27], and non-Hodgkin's lymphoma [28]. However, non significant correlation between the polymorphism and polycystic ovary syndrome [29], cervical cancer [30], periodontal diseases [31] has been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 rs1800896 polymorphism G allele has been shown to cause higher IL-10 production [10], which may further lead to carcinogenesis. Some studies have illustrated that the IL-10 rs1800896 polymorphism was correlated with enhanced risk of nasopharyngeal carcinoma [25] and gastric cancer [26], diabetic nephropathy [27], and non-Hodgkin's lymphoma [28]. However, non significant correlation between the polymorphism and polycystic ovary syndrome [29], cervical cancer [30], periodontal diseases [31] has been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…One such gene possibly associated with HCC is IL-10. Previous studies have reported associations between polymorphisms of this gene and the development of cancers, as well as several other diseases, including acute pancreatitis, coronary artery disease, and colorectal, gastric, oral, lung, esophageal, and breast cancers (Miteva et al, 2014;Qi et al, 2014;Hsu et al, 2015;Jia et al, 2015;Kumar et al, 2015;Vinod et al, 2015;Xu and Liu, 2015;Yang and Fa, 2015;Zhang et al, 2015b). For instance, Miteva et al (2014) reported that the IL-10 -1082A/G polymorphism has a significant impact on the development of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Miteva et al (2014) reported that the IL-10 -1082A/G polymorphism has a significant impact on the development of colorectal cancer. Qi et al (2014) conducted a meta-analysis of 12 studies, finding that the -592G/A variant correlates with increased risk of gastric cancer among Asians, while Hsu et al (2015) reported that Taiwanese carriers of the -819T/C CT genotype have a 3.32-fold increased risk of oral cancer. Moreover, Zhang et al (2015b) observed that the IL- Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine downregulates the production of pro-inflammatory cytokines by inhibition of Th 1 lymphocytes and stimulation of B, as well as Th 2, lymphocytes and thus downregulates the inflammatory response[212,213]. Since 2003 researchers have consistently reported associations between IL-10-592 A/C SNP and susceptibility to gastric cancer but with mixed or conflicting results[217]. A meta-analysis performed by Ni et al[218] indicated that in Asian populations the carriers of IL-10 -1082 GG-plus-GA genotypes are more susceptible to all types of gastric cancer.…”
Section: Inflammation Driven Malignancy Riskmentioning
confidence: 99%